Personal Branding Nadya Shavira Pada Instagram Dalam Membangun Kepercayaan Konsumen Camille Beauty - Esa Sulistyaning Kurniaty; Sari Ekowati (CV Edujavare Publishing, 2026)
Social media, particularly Instagram, has become an effective platform for building personal branding while enhancing consumer trust in a brand. This study aims to analyze how Nadya Shavira's personal branding on Instagram contributes to building consumer trust in Camille Beauty. This research employed a qualitative descriptive method with a constructivist paradigm. Data were collected through observation, in-depth interviews, documentation, and literature review. The research involved one key informant, the Social Media Specialist of Nadya Shavira, and two supporting informants who were followers of Nadya Shavira's Instagram account. Data were analyzed using content analysis based on the dimensions of personal branding, namely authenticity, differentiation, consistency, and visibility, as well as the dimensions of consumer trust, including credibility, integrity, expertise, and benevolence. The findings indicate that Nadya Shavira's personal branding successfully creates an authentic, consistent, and recognizable image through Instagram content and interactions. These dimensions contribute to strengthening consumer trust by enhancing perceptions of her credibility, integrity, expertise, and benevolence. Therefore, consistently managed personal branding on Instagram plays an important role in building consumer trust in Camille Beauty.